1996
DOI: 10.1086/262043
|View full text |Cite
|
Sign up to set email alerts
|

International Differences in Male Wage Inequality: Institutions versus Market Forces

Abstract: While changes in the demand for skilled labor appear to have led to a widening of the wage structures in many countries during the 1980s, considerable differences in the level of wage inequality remain. In this paper, we examine the sources of these differences, focusing primarily on explaining the considerably higher level of wage inequality in the U.S. We fmd that the greater overall dispersion of the U.S. wage distribution reflects considerably more compression at the bottom of the disthbution in the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
398
5
11

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 579 publications
(432 citation statements)
references
References 23 publications
18
398
5
11
Order By: Relevance
“…This conclusion is consistent with cross-country evidence, see Teulings (1999). The results counter the argument of Blau and Kahn (1996) that collective bargaining equalises on observable characteristics and leaves inequality from unobserved characteristics unaffected.…”
Section: Insert Table 5 Around Here]contrasting
confidence: 81%
See 1 more Smart Citation
“…This conclusion is consistent with cross-country evidence, see Teulings (1999). The results counter the argument of Blau and Kahn (1996) that collective bargaining equalises on observable characteristics and leaves inequality from unobserved characteristics unaffected.…”
Section: Insert Table 5 Around Here]contrasting
confidence: 81%
“…At the mean firm size for firms 7 Brown and Medoff (1989) Table 3 shows that the wage structure in the uncovered sector does not come out as markedly different from the bargaining sector. The only outstanding effect is the gender gap; this is a commonly found effect of collective bargaining (Teulings and Hartog, 1998;Blau and Kahn, 1996) The regime that really stands apart is firm bargaining where we find the largest differences in coefficients compared to the other regimes. The firm bargaining regime is more idiosyncratic than the no-bargaining regime.…”
Section: Comparing Firm Bargaining Regimesmentioning
confidence: 54%
“…In several developed countries, public work contributes to reduced inequality (BLAU AND KAHN, 1996;GUSTAFSSON and JOHANSSON, 1999;MILANOVIC, 1994). This is not the case in Brazil.…”
Section: Public Sector Wagesmentioning
confidence: 99%
“…These studies found that public work contributes to reduced inequality (BLAU and KAHN, 1996;GUSTAFSSON and JOHANSSON, 1999;MILANOVIC, 1994), that strong unions and centralized bargaining of wages typical of public workers are determinants of lower levels of income inequality (CHECCHI and GARCÍA-PEÑALOSA, 2010;GOTTSCHALK and SMEEDING, 1997;GUSTAFSSON and JOHANSSON, 1999) and that corporatist welfare state policies are more capable of reducing inequality than targeted policies because of the "paradox of redistribution", that is, (contributory) universalism legitimizes more spending than targeting and it is the level of expenditures that matters most to inequality (GOUDSWAARD and CAMINADA, 2010;KORPI and PALME, 1998;MAHLER and JESUIT, 2006;SMEEDING, 2005).…”
mentioning
confidence: 97%
“…6 As a general matter, international comparisons show that stronger unions and higher levels of collective bargaining are associated with a narrower wage and earnings spread, as are more stringent employment protection laws (Blau and Kahn, 1996). Those narrower wage spreads reduce labour force participation rates, especially among the unskilled (Blau and Kahn, 1996). Moreover, while employment protection laws reduce the rate at which protected workers transition to unemployment, they increase the duration of those spells of unemployment, with the second effect being greater than the first (Blanchard and Portugal, 1998).…”
Section: Not All Reductions In Inequality Are Good For Youmentioning
confidence: 99%